Development of Methods for the Selective Measurement of the Single Amino Acid Exchange Variant Coagulation Factor IX Padua - Weber, Alfred (Mol Ther Methods Clin Dev, 2018)
The description of hyper-functional factor IX (FIX) Padua triggered the development of BAX 335, an AAV8-based hemophilia B gene therapy vector designed to compensate for low FIX protein expression levels by expressing the FIX Padua variant, thereby reducing the exposure to viral vector. The presence of inactive FIX protein at baseline hindered conventional FIX:Ag ELISA from contributing to a more profound understanding of clinical data from the BAX 335 Phase 1/2 study (ClinicalTrials.gov: NCT01687608). By applying phage display technology, a Fab2 mini-antibody selectively binding to FIX Padua was developed and used to establish a FIX Padua-specific ELISA. The assay adequately performed, utilizing human and monkey plasma samples, and enabled the selective quantification of FIX Padua protein in human plasma samples from the BAX 335 trial. The mini-antibody also allowed the development of a chromogenic FIX Padua-specific activity assay, which adequately performed in human and mouse plasma. Collectively, the isolated FIX Padua-specific mini-antibody enabled the development of transgene-product-specific assays, which should improve the monitoring of hemophilia B gene therapies. The approach applied here for FIX Padua could be leveraged to develop variant-specific activity assays for other therapies where highly active enzymes are instrumental in achieving therapeutic levels of the transgene product.